Mindfulness for dummies - Alidina, Shamash (John Wiley & Sons, Ltd., 2015)
Are you suffering from anxiety, depress or debilitating pain? Alidina shows you how mindfulness can help calm jittery nerves, reduce stress and pain, free the mind of distracting thought-- and reignite your perception of this mystery called life.
Includes index. - ''Making Everything Easier!''--Cover. - Online resource; title from PDF title page (ebrary, viewed November 24, 2014)
Keywords: Self-actualization (Psychology); Awareness; Meditation; Psychology, Industrial; Prise de conscience; Méditation; Psychologie du travail